Molecular discrimination of G1 and G3 genotypes of Echinococcus granulosus sensu stricto obtained from human, cattle, and sheep using the mitochondrial NADH dehydrogenase subunit 5 marker - Celik, Figen; Selcuk, Muhammed Ahmed; Kilinc, Seyma Gunyakti; Kesik, Harun Kaya; Ahmed, Haroon; Wang, Ying; Cao, Jianping (Elsevier, 2024)
Cystic echinococcosis (CE) is a common zoonotic disease caused by the larval form of Echinococcus granulosus sensu lato. This study determined the genotype and haplotype differences using the NADH dehydrogenase subunit 5 gene in hydatid cyst samples. Human (n = 12), cattle (n = 28), and sheep (n = 31) hydatid cyst isolates were included. Seventy-one genomic DNA samples were successfully extracted, and a 759 bp mitochondrial NADH dehydrogenase subunit 5 gene fragment was amplified by PCR. Following the sequence analysis, E. granulosus sensu stricto isolates were identified as G1 (n = 61) and G3 (n = 10). A total of 23 haplotypes were obtained from the 71 E. granulosus s.s. G1 and G3 samples. The main haplotype was Hap01 (60.56 %), which consisted of the G1 genotype. The second largest haplotype was Hap04, which consisted entirely of the G3 genotype. Hap14 acted as a bridge between the G1 and G3 genotypes. This study identifies G1 as the dominant genotype in humans and farm animals in Turkey. High haplotype and nucleotide diversity in genotypes were observed. Additionally, this is the first report on the phylogeography and gene flow models of the E. granulosus s. s. population in Turkey using the NADH dehydrogenase subunit 5 gene, the best marker distinguishing between G1 and G3 genotypes.
Keywords: Echinococcus granulosus sensu stricto; NADH dehydrogenase subunit 5; G1 and G3 genotypes; Sheep; Cattle; Human